The River Goddess and Melody-Makers in Nigeria: A Cultural View on Majek Fashek and Victor Uwaifo - Osakue Stevenson Omoera; Daniel Eromosele Omoruan (Modern Africa, 2019)
The art of music-making is a mental/creative activity. However, spiritual influence cannot be ruled out in the process of constructing music. The mental activity is akin to the deployment of the intellect, while the spiritual influence could be as a result of a direct encounter or impartation by a spirit being through dream/vision as typified by two Nigerian performing artists, Majek Fashek and Victor Uwaifo, who are the foci of this study. Exploring the concept of esotericism with emphasis on music performance, this article contends that although music-making is a mental/creative activity, spiritual or extra-mental influences supervene, with particular reference to the lives and performance careers of the two selected African musicians/media celebrities from Benin City in Nigeria. In doing this, it uses historical-analytic, key informant interview (KII), and direct observation methods to critically reflect on how the supernatural influences their music-making activities.